Analyzing Early Feedback: Survey Findings from Elementary Teacher Candidates for AI Comic Development Training Workshop - Ibrahim Ibrahim; Muhammad Syazali; Gita Prima Putra (Pusat Publikasi Ilmiah, STKIP Taman Siswa Bima, 2024)
This research aims to investigateinterest and readiness of prospective elementary school (SD) teachers towards training workshopscomic-based developmentArtificial Intelligence (AI). Through surveysof 104 respondents, data was collected and analyzed to evaluatethe level of interest, obstacles faced, and the urgency of such training.The results show that the majority of respondents (49%) expressed readinessto take part in the workshop, while 48.1% gave the answer